A bibliometric analysis of inflammation and thyroid carcinoma: research trends and future perspectives - Yanhui Feng; Caiqi Huang; Xiaoman Liu; Zhesi Xiao; Lu Wang; Zhengjia Lu; Jia Ming (Frontiers in Oncology, 2025)
Background and objectivesThyroid carcinoma, one of the most prevalent endocrine malignancies, has witnessed a gradual increase in incidence in recent years. Accumulating evidence has demonstrated that inflammation plays a pivotal role in the pathogenesis, progression, and prognosis of thyroid carcinoma, with a significant association between certain malignancies and chronic inflammatory processes. This study conducts a bibliometric analysis of literature on inflammation and thyroid carcinoma over 24 years, aiming to identify trends and research dynamics. The findings are expected to deepen understanding of thyroid carcinoma mechanisms and guide new therapeutic strategies.MethodsWe used the advanced search function of the Web of Science Core Collection to systematically screen and curate articles on inflammation and thyroid carcinoma published between 2000 and 2024. Using Microsoft Excel 2019, we analyzed and visualized publication volume and growth trends. For co-occurrence and clustering analysis of countries, institutions, authors, journals, references, and keywords, we employed VOSviewer, CiteSpace, and the ‘bibliometrix’ package in R. Keyword visualization identified 10 major clusters, including sodium iodide symporter, total thyroidectomy, peroxisome proliferator-activated receptor, papillary thyroid microcarcinoma, therapeutic radiopharmaceuticals, zoological gardens, endoscopic thyroidectomy, mixed cryoglobulinemia, fine needle aspiration, and clinical evaluation. The most frequent keywords were cancer, thyroid cancer, and inflammation.ResultsWe included a total of 1,441 articles published between 2000 and 2024, contributed by 8,326 authors from 2,054 institutions across 70 countries. These articles were published in 625 journals, encompassing 59,808 references and 6,340 keywords. The publication output demonstrated a consistent upward trend over the study period. Among the contributing nations, China emerged as the most prolific country in terms of publication volume. The leading institution was the University of Pisa in Italy. The most productive author was Antonelli, Alessandro, and the leading journal was Thyroid.ConclusionThis bibliometric analysis shows that research on inflammation and thyroid carcinoma is a rapidly evolving field, marked by diverse themes and in-depth studies. Advances in technology and extensive research are expected to clarify how inflammation drives thyroid carcinoma initiation and progression. This deeper understanding will lead to new approaches in diagnosis, prevention, and treatment of thyroid carcinoma.